Research Thinking for Responsive Teaching Research Skill Development with In-service and Preservice Educators - Willison, John (SpringerBriefs in Education,, 2024)
This open access book examines the facilitation of pre-service and in-service educators' research thinking that equips them to be responsive to the unfolding uncertainties of the 21st century, and to likewise prepare their own students. It addresses several key areas, including: articulating the contemporary need for research thinking across teacher education; showcasing diverse yet conceptually connected strategies that all use the Research Skill Development (RSD) framework; providing an explicit scaffolded approach; and extending knowledge of the 'Models of Engaged Learning and Teaching' (MELT) conceptual framework. This book also addresses the contemporary topics of social media for learning, digital literacy, education research as cultural work and formations of communities of practice, with cross-cutting themes of scaffolded development and formative assessment of research skills. It highlights how research thinking is not only vital for PST (Preservice Teachers), I-ST (In-Serivce Teachers) and university educators, but also models for them how to scaffold the research thinking of their own students. This book's use of the RSD, as a shared conceptual framework across the chapters, emphasises the overlaps between ways of thinking in the different learning areas in which education occurs, without masking the differences. Likewise, the interdisciplinary work that comprises Education is informed by the RSD conceptual framework as used in a variety of disciplines. Together, this use of RSD brings a strong sense of connectedness between PST, I-ST and university educators. This is an open access book.